The broken cord - Dorris, Michael A. 1945-1997 (Harper & Row, 1989)
Author Michael Dorris explains how traditions of spirit and memory weave through the lives of many Native Americans and how alcoholism and despair have shattered so many lives. Also chronicles the effects of fetal alcohol syndrome on their adopted son and on the Native American community as a whole.
Keywords: Family -- psychology; Fetal Alcohol Syndrome; Fetal alcohol syndrome -- Patients -- Family relationships; Fetal alcohol syndrome -- Patients -- United States -- Biography; Indianer; Kind; Adoption; Fetale Alkoholspektrumstörung; USA; Nordamerika; Biografie; Erlebnisbericht